2005
DOI: 10.1097/01.ta.0000151270.26634.dd
|View full text |Cite
|
Sign up to set email alerts
|

Skiing- and Snowboarding-Related Injuries Treated in U.S. Emergency Departments, 2002

Abstract: Our study is the first to demonstrate that older skiers are at highest risk for injury. Adolescents are at highest risk for snowboarding-related injury. Prevention of TBI should be a top injury control priority among skiers and snowboarders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
64
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 25 publications
7
64
0
Order By: Relevance
“…There are four main causes of TBI: traffic accidents [1], work and sports accidents [2,3], and violence [4,5]. Recent data suggest that anterior pituitary dysfunction is common after TBI.…”
Section: Introductionmentioning
confidence: 99%
“…There are four main causes of TBI: traffic accidents [1], work and sports accidents [2,3], and violence [4,5]. Recent data suggest that anterior pituitary dysfunction is common after TBI.…”
Section: Introductionmentioning
confidence: 99%
“…Selection of an appropriate denominator for injury rates can have a major impact on final conclusions. For example, Xiang et al 35 found that age-specific injury-rate differences calculated by using the number of snow-skiing participants as the denominator disappeared when US census population estimates were used as the denominator. This led to their conclusion that, especially in sports-and recreation-related injury research, participation data more accurately reflect risk exposure and are more appropriate for calculating injury rates.…”
Section: Limitations Of Studymentioning
confidence: 99%
“…Snowboarders are affected by other types of injuries and they also experience a higher injury rate of 4-16 injuries per 1000 snowboarder days (7). In the literature, it is widely accepted that snowboarders are at an increased risk of head and upper arm injuries, chiefly wrist injuries (4,(8)(9)(10)(11). Skiing accidents in different countries may not always follow the same pattern of injury or incidence.…”
Section: Introductionmentioning
confidence: 99%